2017
DOI: 10.1027/1618-3169/a000359
|View full text |Cite
|
Sign up to set email alerts
|

The Intention-Outcome Asymmetry Effect

Abstract: Knowledge of intention and outcome is integral to making judgments of responsibility, blame, and causality. Yet, little is known about the effect of conflicting intentions and outcomes on these judgments. In a series of four experiments, we combine good and bad intentions with positive and negative outcomes, presenting these through everyday moral scenarios. Our results demonstrate an asymmetry in responsibility, causality, and blame judgments for the two incongruent conditions: well-intentioned agents are reg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 55 publications
0
8
1
Order By: Relevance
“…Finally, unlike prior research with adults (Knobe, 2003;Sarin et al, 2017), we did not find an asymmetry in participants' attributions of blame and praise. Adults assigned blame (94%) in the bad intent condition and praise (94%) in the good intent condition to the same extent.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Finally, unlike prior research with adults (Knobe, 2003;Sarin et al, 2017), we did not find an asymmetry in participants' attributions of blame and praise. Adults assigned blame (94%) in the bad intent condition and praise (94%) in the good intent condition to the same extent.…”
Section: Discussioncontrasting
confidence: 99%
“…Unfortunately, the dress ended up fitting very poorly and her THEORY OF MIND AND MORAL DEVELOPMENT 9 sister got bullied at school for it (good intention, bad side-effect). Knobe (2003; see also Sarin et al, 2017) found that individuals are more likely to say that a negative side effect was brought on intentionally (and is therefore blameworthy) compared to a side effect that is positive.…”
Section: Contextsmentioning
confidence: 99%
“…In that sense, our judgment of interest, causal-responsibility, is similar to judgments of causal strength (but note that we focus on judging the responsibility of agents for an outcome of their actions). Probing causal strength typically asks "to what extent X caused Y, " while probing causal responsibility asks "how responsible is X for Y" (Sarin et al, 2017). Indeed, most studies in the field have probed participants with either of these measures with parallel effects (Murray and Lombrozo, 2017;Sarin et al, 2017).…”
Section: Judgments Of Causation Vs Judgments Of Responsibilitymentioning
confidence: 99%
“…Probing causal strength typically asks "to what extent X caused Y, " while probing causal responsibility asks "how responsible is X for Y" (Sarin et al, 2017). Indeed, most studies in the field have probed participants with either of these measures with parallel effects (Murray and Lombrozo, 2017;Sarin et al, 2017). Moreover, Sytsma et al (2012) have proposed that "the ordinary concept of causation, at least as applied to agents, is an inherently normative concept: Causal attributions are typically used to indicate something more akin to who is responsible for a given outcome than who caused the outcome in the descriptive sense of the term used by philosophers" (p. 815).…”
Section: Judgments Of Causation Vs Judgments Of Responsibilitymentioning
confidence: 99%
“…We previously showed that paranoia involves an increased attribution of harmful intent to others and an increased tendency to punish selfish partners (Raihani & Bell, 2018). Punishment decisions are known to depend not just on whether harm occurred but on the perception of whether the harm was intended (Cushman et al, 2009; Gerstenberg et al, 2011; Sarin et al, 2017; Schaechtele et al, 2011). In this previous work, increased punitive tendency in paranoia was partly (but not fully) mediated by the tendency to attribute harmful intent to others.…”
mentioning
confidence: 99%